2019
DOI: 10.24931/2413-9432-2019-8-1-38-45
|View full text |Cite
|
Sign up to set email alerts
|

Laser fluorescence spectroscopy and optical tissue oximetry in the diagnosis of skin fibrosis

Abstract: There are currently no effective measures to combat fibrosis in modern medical practice. One of the reasons for that is the late diagnosis associated with the lack of available clinical biomarkers and effective methods of non-invasive detection of the process. Fibrosis of the skin is characterized by fibrosis of the dermis, underlying tissues and is represented by a wide range of nosologies. Scleroderma and scars are of the greatest interest for the study. Skin changes in the development of bleomycin-induced f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In addition, the pulse oximetry method allows obtaining information about the only saturation level in the blood. At the same time, the studies show that information on the state of the microcirculation system in biological tissues is often needed both in different parts of the body and at different depths [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the pulse oximetry method allows obtaining information about the only saturation level in the blood. At the same time, the studies show that information on the state of the microcirculation system in biological tissues is often needed both in different parts of the body and at different depths [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, our recent studies in animals have shown that the tissue porphyrin content index in biological tissues calculated by means of the registered fluorescence spectra reflects the dynamics of the local acute inflammatory process [9]. In combination with the optical tissue oximetry, LFS allows us to define quantitatively the stage of the fibrosis development and the prevailing pathological process (inflammation/ hypoxia/fibrosis) [10].…”
Section: Introductionmentioning
confidence: 99%